The Relationship Between Work Posture, Workload, and Sex with Musculoskeletal Disorder (MSDs) Complaints in Workers at Tofu Factories in Piyungan District - Rosita Denavia, Herlin; Dwi Saptadi, Julian (Periodicals of Occupational Safety and Health, 2024)
Background: Musculoskeletal Disorder is a disease or complaint that occurs in parts of the skeletal muscles that are felt by a person ranging from very mild complaints to very severe complaints. MSDs complaints can be caused by several factors such as work posture, workload, gender, age, body size, and so on. Therefore, this study aims to determine the relationship between gender, workload, and work posture to MSDs complaints felt by workers in tofu factories in the Piyungan District area. Methods: This study used a quantitative method. observational analysis of cross sectional  design design.Cross sectional design is a research design by measuring or observing at the same time exposure to variables, with a case study design of workers in sections. This study used the REBA method, SNI 7269:2009 standard measurement, and Nordic Body Map  questionnaire to see worker complaints Results: There was a significant relationship between work posture and complaints of Musculoskeletal Disorder in tofu manufacturing workers in Piyungan District with a p-value of 0.050 (p-value<0.05). There was a significant relationship between workload and complaints  of Musculoskeletal Disorder in tofu manufacturing workers in the Piyungan District area with a p-value of 0.041 (p-value<0.05). There was a significant relationship between sex and complaints  of Musculoskeletal Disorder in tofu manufacturing workers in the Piyungan District area with a p-value of 0.050 (p-value<0.05). Conclusion: This study shows a significant relationship between work posture, workload, and gender and complaints of Musculoskeletal Disorder in tofu making in Piyungan District.